2018
DOI: 10.1001/jamainternmed.2018.3056
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Overdiagnosis of Lung Cancer in Low-Dose Computed Tomography Screening

Abstract: Denmark, contributed with data acquisition and received financial compensation for her work. 1. Pedersen JH, Ashraf H, Dirksen A, et al. The Danish randomized lung cancer CT screening trial: overall design and results of the prevalence round.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 6 publications
0
62
0
2
Order By: Relevance
“…20 Screening for specific cancer types, like prostate (PSA testing), 41,42 lung (low-dose computed tomography), 43,44 and breast (mammography) 45,46 have available evidence and potential risks associated with overdiagnosis; however, the magnitude of risk associated with overdiagnosis remains highly variable. [41][42][43][44][45][46] This magnitude of risk may be of particular concern for cancer types with conflicting recommendations and guidelines regarding initiation and frequency of screening. 18 Communicating overdiagnosis in PDAs may not be as high of a concern among other cancer types that have lower magnitude of risk for overdiagnosis, such as with colorectal cancer screening based on US recommendations and guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…20 Screening for specific cancer types, like prostate (PSA testing), 41,42 lung (low-dose computed tomography), 43,44 and breast (mammography) 45,46 have available evidence and potential risks associated with overdiagnosis; however, the magnitude of risk associated with overdiagnosis remains highly variable. [41][42][43][44][45][46] This magnitude of risk may be of particular concern for cancer types with conflicting recommendations and guidelines regarding initiation and frequency of screening. 18 Communicating overdiagnosis in PDAs may not be as high of a concern among other cancer types that have lower magnitude of risk for overdiagnosis, such as with colorectal cancer screening based on US recommendations and guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…In our literature search, we identified the nine trials investigating LDCT screening, of which we already knew (table S1) [17,[23][24][25][26][29][30][31][32]. This paper was first submitted to the journal Breathe on 20 January 2020.…”
Section: Resultsmentioning
confidence: 99%
“…The Italian Lung Cancer Screening trial (ITALUNG) revealed no overdiagnosis, which indicates that this trial was either biased and/or that CT screening was limited in its ability to detect the earliest-stage lung cancers [97]. The Danish Lung Cancer Screening Trial (DLCST) concluded that 67.2% of screening-detected cancers were overdiagnosed, with little degree of contamination bias but a potential minor uneven distribution at randomisation: more heavy smokers and participants with COPD in the intervention group [98]. The most recent NELSON results did not disclose the estimate of overdiagnosis; however, the cumulative incidences of lung cancer in the intervention and control arms indicated some degree of overdiagnosis [15].…”
Section: Overdiagnosis and Harmsmentioning
confidence: 97%
“…The estimate of overdiagnosis is prone to bias [93] because it is linked to a pathological reference standard [94]. Thereby, several metrics become altered, including diagnostic test accuracy, incidence and prevalence, stage shift and survival rates [95]. The degree of overdiagnosis should be accounted for when using risk models and estimating outcomes.…”
Section: Overdiagnosis and Harmsmentioning
confidence: 99%
See 1 more Smart Citation